STUDI LABORATORIUM : ANALISA ALIRAN DUA FASA DENGAN MENGGUNAKAN APLIKASI JET GAS LIFT PADA METODE SMALL TUBE LIQUID-LIFTING TECHNIQUE UNTUK PENANGGULANGAN LIQUID LOADING - Aditya, Wisnu
In gas wells with depleting reservoir pressure, liquid loading can be happened because the gas rate is no longer above the gas critical velocity. Liquid loading can be a serious problem because the liquid accumulation on the bottom of the well can reduce gas flow rate and moreover, the well can be dead. To solve this problem, deliquification processs such as compression, swabbing, velocity string, foaming, pump modification, downhole separation and injection (intermittent production), heated tubing application etc. is needed. Velocity string use the small tube principle to increase gas rate inside the small diameter pipe. Small velocity string diameter can causing high friction on it. Therefore, velocity string is not efficient to be used in wells with the low pressure. In this study, Jet Gas Lift application on Small Tube Liquid-Lifting Technique (STLT) method is used in deliquification process. Jet gas lift application on STLT method is a modification of STLT method by changing the tubing hole design from STLT method with jet gas lift design. From the obtained data, jet gas lift application on STLT method has the better deliquification result than the STLT method with the same pipe diameter. In this study, the effect of pipe diameter and angle in extension pipe variation to gas and liquid rate is observed.